Pelatihan Penerapan Teknologi Pengolahan Pangan pada Komoditas Jagung di STT-SAPPI Ciranjang Kabupaten Cianjur - Siregar, Tagor M.; Wijaya, Julia Ratna; Natania, Natania; Mastuti, Titri Siratantri; Sanaky, Florecita; Teo, Claudius; Julian, Beatrice (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2025)
The Indonesian School of Biblical Studies for Rural Development is a Theological College, where graduates are expected to play an active role in community empowerment. In this regard, the Food Technology Study Program of Pelita Harapan University (UPH) conducted Community Service (PkM) in the form of Training on the Application of Food Processing Technology to Corn Commodities. This activity was carried out through preparation and implementation stages. In the preparation stage, trials of the processing process and formulation determination were carried out and corn-based processed products were obtained in the Food Processing Laboratory. The results of this stage were formulated into part of the training material in the form of descriptions and explanations of materials, tools, processing procedures including material preparation, drying, manufacturing processes and determining the formulation of corn-based food products, namely corn flour, tortilla chips, and instant corn soup. In the implementation stage, the PkM team presented, explained and practiced the prepared training materials to students at STT-SAPPI Cianjur, West Java. The training was conducted on April 24, 2025, by a seven-person Community Service (PkM) team consisting of four lecturers, one teaching assistant, and two students from the UPH Food Technology Study Program. Twenty-five participants, including students from STT-SAPPI Ciranjang, Cianjur Regency, participated in the training. Evaluation of the training, based on questionnaires, showed that all (100%) participants found the training to be successful and very beneficial.